2008
DOI: 10.1007/s00268-008-9540-x
|View full text |Cite
|
Sign up to set email alerts
|

Stapled Transanal Rectal Resection for Outlet Obstruction Syndrome: Results and Follow‐up

Abstract: According to the present study, STARR seemed to be a safe and effective treatment for OOS associated with symptomatic rectocele and intussusception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
4
3

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 32 publications
1
27
4
3
Order By: Relevance
“…Conversely, Renzi,et al 19 reported no significant difference between pre-and postoperative rectal sensitivity parameters despite the correction of rectocele and a successful clinical outcome in 61 of 68 patients (89.7%). Similar findings have recently been reported by Frascio, et al, 23 who found that the preoperative subjective rectal sensitivity threshold volume (defecation stimulus) was within normal ranges (61.8 Ϯ 14.3 mL) and the maximum tolerable volume (threshold of evoked abdominal pain) was rather low (69.8 Ϯ 38.9 mL), suggesting an increased rectal sensitivity that seems in contrast with expected findings in patients with ODS. Moreover, their postoperative rectoanal reflex study indicated an unchanged threshold of defecation stimulus and a significant increase in the threshold of evoked abdominal pain, suggesting (from the manometric standpoint) a decreased rectal sensitivity with a potential worsening of ODS symptoms.…”
Section: Discussioncontrasting
confidence: 55%
“…Conversely, Renzi,et al 19 reported no significant difference between pre-and postoperative rectal sensitivity parameters despite the correction of rectocele and a successful clinical outcome in 61 of 68 patients (89.7%). Similar findings have recently been reported by Frascio, et al, 23 who found that the preoperative subjective rectal sensitivity threshold volume (defecation stimulus) was within normal ranges (61.8 Ϯ 14.3 mL) and the maximum tolerable volume (threshold of evoked abdominal pain) was rather low (69.8 Ϯ 38.9 mL), suggesting an increased rectal sensitivity that seems in contrast with expected findings in patients with ODS. Moreover, their postoperative rectoanal reflex study indicated an unchanged threshold of defecation stimulus and a significant increase in the threshold of evoked abdominal pain, suggesting (from the manometric standpoint) a decreased rectal sensitivity with a potential worsening of ODS symptoms.…”
Section: Discussioncontrasting
confidence: 55%
“…3 The aim of STARR is to correct the mechanical outlet obstruction caused by rectal intussusception and/or rectocele by use of a stapler device for endorectal resection of the distal rectum. 4,5 A specifically designed stapler, the Contour30-Transtar has recently been introduced for STARR. 6 We have previously shown that Contour30-Transtar is as safe and effective as the double-stapling PPH-STARR technique and, in comparison, it allows the opportunity to resect almost twice the amount of tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the functional outcomes following STARR are often based on patient-reported questionnaires, which are subjective and liable to study biases. 5 Few objective data concerning the anatomical changes resulting from STARR have been made available, 4,8 and this is particularly so for the newer Contour30 Transtar device. So far, there has been no attempt to correlate the radiological changes associated with STARR with postoperative changes in constipation and incontinence.…”
Section: Resultsmentioning
confidence: 99%
“…Einheitliche oder international anerkannte Kriterien für die diversen konservativen und operativen Therapieoptionen sind nicht formuliert, so dass die publizierten Studien zu dieser Thematik extrem heterogen sind. Besonders kontrovers wird in diesem Zusammenhang natürlich die Wertigkeit der STARR-Operation diskutiert [6,7,8].…”
Section: Originalpublikationunclassified